The state of routine and emergency obstetric and neonatal care in Southern Province, Zambia. Issue 1 (January 2015) - Owens, Lauren; Semrau, Katherine; Mbewe, Reuben; Musokotwane, Kebby; Grogan, Caroline; Maine, Deborah; Hamer, Davidson H.
Abstract: Objective: To evaluate the capacity of health facilities in Southern Province, Zambia, to perform routine obstetric care and emergency obstetric and neonatal care (EmONC). Methods: Surveys were completed at 90 health centers and 10 hospitals between September 1, 2011, and February 28, 2012. An expanded set of signal functions for routine care and EmONC was used to assess the facilities' capacity to provide obstetric and neonatal care. Results: Interviews were completed with 172 health workers. Comprehensive EmONC was available in only six of 10 hospitals; the remaining four hospitals did not perform all basic EmONC signal functions. None of the 90 health centers performed the basic set of EmONC signal functions. Performance of routine obstetric care functions, health worker EmONC training, and facility infrastructure and staffing varied. Conclusion: Assessment of the indicators for routine care revealed that several low-cost interventions are currently underused in Southern Province. There is substantial room for improvement in emergency and routine obstetric and neonatal care at the surveyed facilities. Efforts should focus on improving infrastructure and supplies, EmONC training, and adherence to the UN guidelines for routine and emergency obstetric care.